2020
DOI: 10.1186/s13104-020-05007-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of antenatal stress in Pakistan: perspectives from a developing country

Abstract: Objective: Antenatal stress is highly prevalent globally and is associated with adverse physical and psychiatric morbidities and adverse neonatal outcomes. However, the burden of antenatal stress and its psychosocial predicators have not been explored in context of the Pakistani sociocultural environment. The present study explores the prevalence of antenatal stress and its association with gender of offspring, socioeconomic background, cultural beliefs, and access to healthcare in the province of Punjab, Paki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 21 publications
0
34
1
4
Order By: Relevance
“…There was no relationship in the Saudi study (Ahmed et al, 2017) between number of children and perceived stress and in a study in Tehran-Iran (Kashanian et al, 2019) between unwanted pregnancy and perceived stress of pregnant women. However, in the study of pregnant Pakistani women, unwanted pregnancy and having more children were identified as predictors of stress (Waqas et al, 2020). Secondary analysis of a prospective cohort study in the United States has also shown that unwanted pregnancies was associated with higher perceived stress in pregnant women (Gariepy et al, 2016).…”
Section: <001mentioning
confidence: 99%
“…There was no relationship in the Saudi study (Ahmed et al, 2017) between number of children and perceived stress and in a study in Tehran-Iran (Kashanian et al, 2019) between unwanted pregnancy and perceived stress of pregnant women. However, in the study of pregnant Pakistani women, unwanted pregnancy and having more children were identified as predictors of stress (Waqas et al, 2020). Secondary analysis of a prospective cohort study in the United States has also shown that unwanted pregnancies was associated with higher perceived stress in pregnant women (Gariepy et al, 2016).…”
Section: <001mentioning
confidence: 99%
“…3 Prevalence of perceived stress in pregnancy varies from 11.6% to 46.7%. [4][5][6][7] However, there have been few worldwide reports of prevalence of antenatal perceived stress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of factors associated with perceived stress were varied and inconclusive, such as gravida, gestational age, family income, pregnancy intention, husband's employment status, medical co-morbidities, and family support. [3][4][5][6][7]14,15 The variety of these factors depends on population, sample size, stress-screening tool, and cultural context.…”
Section: Introductionmentioning
confidence: 99%
“…Situated in this region, the country of Pakistan is home to over 210 million people, making it the sixth most populous nation in the world (UNICEF, 2018). A predominantly Muslim nation, Pakistan is an ethnically diverse country where family units are predominantly patriarchal (Waqas et al, 2020). Although pregnancy in this culture is generally seen as a time of fulfillment and joy, for many it brings a plethora of psychosocial stress, owing to the religio-cultural stigma rooted in gender discrimination and patriarchy (Waqas et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%